2002
DOI: 10.1007/s11661-002-0274-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain boundary characteristics on intergranular corrosion resistance of 6061 aluminum alloy extrusion

Abstract: The intergranular corrosion (IGC) behavior of 6061 aluminum alloy extrusions was investigated. After the IGC test in accordance with ISO/DIS 11846 (method B), heavy IGC was observed at the surface of the extrusion. However, little IGC occurred at the center plane of the extrusion thickness. It was considered that IGC was caused by the existence of precipitate-free zones (PFZs) because PFZs were clearly observed in the surface layer of the extrusion but were not clearly observed in the center position of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(42 citation statements)
references
References 3 publications
3
39
0
Order By: Relevance
“…The reason why the warm rolled sheets containing zirconium have good resistance to SCC may be derived from its microstructure. In the previous study on AA6061 alloy extrusions, 13) it was suggested the formation of a precipitate free zone (PFZ) is restrained at a low angle boundary, which leads to high resistance to intergranular corrosion. Figure 11 shows TEM images of the samples in T6 condition and Kikuchi patterns derived from two grains facing each other across a grain boundary.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why the warm rolled sheets containing zirconium have good resistance to SCC may be derived from its microstructure. In the previous study on AA6061 alloy extrusions, 13) it was suggested the formation of a precipitate free zone (PFZ) is restrained at a low angle boundary, which leads to high resistance to intergranular corrosion. Figure 11 shows TEM images of the samples in T6 condition and Kikuchi patterns derived from two grains facing each other across a grain boundary.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the pinning effect of nano-sized Al 3 (Sc, Zr) particles on the movement of the grain boundaries [26], dynamic recrystallization of Al-Zn-Mg alloy during hot extrusion is inhibited. Compared with high-angle recrystallization grain boundary, low-angle subgrain boundary with lower grain boundary energy inhibits the formation of GBPs and PFZ [13], so Sc addition reduces the width of PFZ and transforms GBPs from continuous distribution into interrupted distribution for Al-Zn-Mg alloy. Figure 3 gives stress-strain curves of two aged alloys tested at a strain rate of 5 × 10 −6 s −1 in different corrosive environments.…”
Section: Methodsmentioning
confidence: 99%
“…7xxx series alloys are mainly applied in the form of rolled plates or extruded sections, and the static or dynamic recrystallization is easy to occur during hot working and heat treatment. Compared with low-angle grain boundary, high-angle recrystallization grain boundary with higher grain boundary energy promotes the nucleation and growth of grain boundary precipitates (GBPs) [13]. Under peak-aged condition, the GBPs distributed continuously along recrystallization grain boundary accelerate corrosion crack propagation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…2b shows that the corrosion is intergranular and occurs much more on the precipitates free zones. T. Minoda et al [11] reported that there is dissolution of the zones PFZs because of the difference between the potential of these zones PFZs and the grain wedges of the precipitates in the matrix. Fig.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%